CONCERNS ABOUT PHYSICAL INACTIVITY AMONG ADOLESCENTS IN THE STRAND, SOUTH AFRICA - Phillips, Julie (Journal of Community and Health Sciences, 2020)
Introduction: Strong evidence exist to support the assumption that regular physical activity is one of the most cost effective interventions for the prevention and management of chronic diseases of lifestyle, and should therefore be widely promoted. However, concerns about physical inactivity among adolescents have been raised in various countries. The levels of habitual physical activity among urbanized South Africans seems no better than what obtains in similarly urbanized populations in other countries. Objective: The aim of the study was to highlight the type of recreational physical activities, as well as the frequency and duration in which learners from the four high schools (n=1042) in the Strand, Western Cape participated in. Methodology: The instrument utilized was a self-administered questionnaire adapted from the one developed by the South Australian Branch of Sports Medicine to determine recreational activities in school children. Results: A high proportion of learners were found to be involved in different recreational physical activities, which included rugby, soccer, netball and walking. However, learners were not participating at a level at which the health benefits of participation could be maximized. Discussion: The outcome of the current study suggests that it is unlikely that the learners maximized the health benefits of participation in physical activities. They may thus be prone to the possibilities of developing chronic diseases of lifestyle. Conclusion: High school learners should routinely be informed about the importance of incorporating physical activity into their lives.